Formulated microbial consortium as inoculant for agarwood induction - Justin, S; Lihan, Samuel; Elvis-Sulang, MR; Chiew, TS (Forest Research Institute Malaysia, 2020)
Agarwood or gaharu is well known as the most valuable resinous heartwood that occurs in trees of Aquilaria species. Depletion of the wild resource from the jungle leads to the high price of agarwood. Thus, there is an urgent need to produce agarwood sustainably through agarwood cultivation to meet the global demand and induction. This research was conducted to formulate microbial consortia that can be used as fungal inoculants for agarwood induction in Aquilaria species. The effectiveness of formulated microbial consortia was observed based on the colour and mean length of infected zone formation after a three and six months inoculation periods in each wet and dry season, respectively. Aquilaria sp. was inoculated with three types of formulated fungal inoculants and negative control by using the bottle drip method. The findings showed that F3 inoculant (a combination of Trichoderma sp., Lasiodiplodia sp. and Curvularia sp.) was the most potential fungal inoculant for agarwood formation based on the darkest colour and largest mean length of the infected zone, after a three and six months inoculation periods for both wet and dry seasons. The formulated inoculant is recommended for further development as agarwood fungal inoculant to induce agarwood artificially for future sustainable supply of agarwood.